The Meaning of the Song “Alamate Anak Sholeh” in the Perspective of Da'wah Message - Indah Sariyanti; Nuris Asro'atul Hasanah; Nidya Agustin Beni Prasetyo (Universitas Darussalam Gontor, 2024)
This article aims to analyze the song